2005
DOI: 10.1104/pp.105.067603
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas fluorescens and Glomus mosseae Trigger DMI3-Dependent Activation of Genes Related to a Signal Transduction Pathway in Roots of Medicago truncatula  

Abstract: Plant genes induced during early root colonization of Medicago truncatula Gaertn. J5 by a growth-promoting strain of Pseudomonas fluorescens (C7R12) have been identified by suppressive subtractive hybridization. Ten M. truncatula genes, coding proteins associated with a putative signal transduction pathway, showed an early and transient activation during initial interactions between M. truncatula and P. fluorescens, up to 8 d after root inoculation. Gene expression was not significantly enhanced, except for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 90 publications
1
48
0
6
Order By: Relevance
“…In roots of the legume species Medicago trunculata, Sanchez et al (2005) found 58 genes to be upregulated in response to colonization by the growth-promoting strain Pseudomonas fluorescens C7R12, a number in line with that found by Verhagen et al (2004) in Arabidopsis roots colonized by strain WCS417. Out of 10 of the C7R12-induced genes, 9 were not upregulated in the M. trunculata dmi3 mutant, which is impaired in the signal transduction pathway of the Nod factor from Sinorhizobium meliloti as well as in mycorrhization by the fungus Glomus mosseae.…”
Section: Expression Of Systemically Induced Resistance In the Plantsupporting
confidence: 49%
“…In roots of the legume species Medicago trunculata, Sanchez et al (2005) found 58 genes to be upregulated in response to colonization by the growth-promoting strain Pseudomonas fluorescens C7R12, a number in line with that found by Verhagen et al (2004) in Arabidopsis roots colonized by strain WCS417. Out of 10 of the C7R12-induced genes, 9 were not upregulated in the M. trunculata dmi3 mutant, which is impaired in the signal transduction pathway of the Nod factor from Sinorhizobium meliloti as well as in mycorrhization by the fungus Glomus mosseae.…”
Section: Expression Of Systemically Induced Resistance In the Plantsupporting
confidence: 49%
“…identified an increase in JA-regulated PR-, salt stress-relatedand putative receptor like-proteins, especially in less-compatible interactions (Miché et al, 2006). In Medicago truncatula the initial local transcriptional responses to the mycorrhizal fungus Glomus mosseae showed significant overlap to those initiated by the PGPR P. fluorescens C7R12 (Sanchez et al, 2005). Moreover, both beneficials were unable to elicit these shared transcriptional responses in the symbiosis-defective mutant dmi3 (does not make infections 3), suggesting that the signaling pathways that are triggered by these different beneficials converge (Sanchez et al, 2005).…”
Section: Local Responses To Beneficial Microbesmentioning
confidence: 99%
“…In rice, 40% of the mycorrhiza-responsive genes were also responsive to infection by fungal pathogens, indicating that the responses to beneficial and pathogenic fungi partly overlap [45]. Interestingly, some of the initial responses of Medicago truncatula to the mycorrhizal fungus Glomus mosseae and to the beneficial rhizobacterium P. fluorescens C7R12 have been shown to be overlapping as well [46]. Both beneficial microbes failed to elicit these shared responses in the symbiosisdefective mutant dmi3, which is affected in the calciumdependent and calmodulin-dependent protein kinase DMI3 [46].…”
Section: Local Immune Responses Triggered By Beneficial Microbesmentioning
confidence: 99%
“…Interestingly, some of the initial responses of Medicago truncatula to the mycorrhizal fungus Glomus mosseae and to the beneficial rhizobacterium P. fluorescens C7R12 have been shown to be overlapping as well [46]. Both beneficial microbes failed to elicit these shared responses in the symbiosisdefective mutant dmi3, which is affected in the calciumdependent and calmodulin-dependent protein kinase DMI3 [46]. Again, this suggests that the signaling pathways triggered by very different beneficial microbes converge.…”
Section: Local Immune Responses Triggered By Beneficial Microbesmentioning
confidence: 99%